Immediate Effect of Kinesiology Tape on Functionality, Static and Dynamic Balance, Exercise Capacity, and Posture in Users of High-Heeled Shoes - SARI, ZÜBEYİR (My University, 2023)
BACKGROUND: Using high-heeled shoes in daily life affects the stability of walking, body posture, and functionality. We aimed to determine the immediate effect of kinesiology taping (KT) on functionality, static and dynamic balance, exercise capacity, and posture in young women using high-heeled shoes. METHODS: Thirty-seven women who wore high-heeled shoes (mean ± SD age, 20.32 ± 1.37 years) were divided into control (n = 20) and study (n = 17) groups. Both limbs of study group participants were taped medially, laterally, and dorsally with KT; no application was made to the control group. Balance (TecnoBody postural line), functionality (vertical jump and functional reach tests), exercise capacity (6-Minute Walk Test), and human body posture (New York Posture Rating Chart) were assessed. RESULTS: Median use of high-heeled shoes was 8 hours daily, 5 days weekly, and 3 years in the study group versus 6 hours daily, 4 days weekly, and 4 years in the control group. Significance in functional reach distance was found within the control (P = .010) and study (P = .005) groups but not between the groups. Stabilometric monopedal right foot ellipse area (P = .016) and perimeter (P = .009); left foot ellipse area (P = .016), perimeter (P = .023), and front/back standard deviation (P = .018); and dynamic balance area gap percentage (P = .030) were significant within the study group. Posture, vertical jump distance, exercise capacity, stabilometric test results, and bipedal closed-eye and opened-eye results were similar within and between groups (P > .05). CONCLUSIONS: Kinesiology taping has no immediate effect on exercise capacity, vertical jump function, posture, and bipedal static balance but can modulate functional reach function, static monopedal leg balance, and dynamic equilibrium. Further studies are recommended to investigate the additive effect of KT with high-heeled shoes and after 45 min, 24 hours, and 72 hours.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine